(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the role of Persian in the historical development of the Uzbek language. It is said that not only words but also some grammatical elements came from Persian. Some verb bases in Uzbek as nouns and adjectives, words expressing place names, Persian suffixes and numbers are widely used in Uzbek. In the Uzbek language, the group of active words in the Uzbek language includes constant words and phrases borrowed from other languages ​​and constituting the material and cultural values ​​of the Uzbek nation, widely used, independent nouns, from which they are derivatives of the language. Over its long history, the Uzbek language has developed and improved its vocabulary, primarily due to internal capabilities, as well as due to words absorbed from other languages. Words that have passed into the Uzbek language from the Persian language are included in the vocabulary of the Uzbek language and obey its grammatical rules. Изучение прямого и переносного значения этих слов позволяет глубже изучить узбекский язык и нашу классическую литературу.